Lamin A/C haploinsufficiency modulates the differentiation potential of mouse embryonic stem cells. - Poonam Sehgal (Public Library of Science (PLoS), 2013)
Background Lamins are structural proteins that are the major determinants of nuclear architecture and play important roles in various nuclear functions including gene regulation and cell differentiation. Mutations in the human lamin A gene cause a spectrum of genetic diseases that affect specific tissues. Most available mouse models for laminopathies recapitulate disease symptoms for muscle diseases and progerias. However, loss of human lamin A/C also has highly deleterious effects on fetal development. Hence it is important to understand the impact of lamin A/C expression levels on embryonic differentiation pathways. Methodology and principal findings We have investigated the differentiation potential of mouse embryonic stem cells containing reduced levels of lamin A/C by detailed lineage analysis of embryoid bodies derived from these cells by in vitro culture. We initially carried out a targeted disruption of one allele of the mouse lamin A/C gene (Lmna). Undifferentiated wild-type and Lmna(+/-) embryonic stem cells showed similar expression of pluripotency markers and cell cycle profiles. Upon spontaneous differentiation into embryoid bodies, markers for visceral endoderm such as α-fetoprotein were highly upregulated in haploinsufficient cells. However, neuronal markers such as β-III tubulin and nestin were downregulated. Furthermore, we observed a reduction in the commitment of Lmna(+/-) cells into the myogenic lineage, but no discernible effects on cardiac, adipocyte or osteocyte lineages. In the next series of experiments, we derived embryonic stem cell clones expressing lamin A/C short hairpin RNA and examined their differentiation potential. These cells expressed pluripotency markers and, upon differentiation, the expression of lineage-specific markers was altered as observed with Lmna(+/-) embryonic stem cells. Conclusions We have observed significant effects on embryonic stem cell differentiation to visceral endoderm, neuronal and myogenic lineages upon depletion of lamin A/C. Hence our results implicate lamin A/C level as an important determinant of lineage-specific differentiation during embryonic development.